The Role of Health-Promoting Behaviors in Predicting the Quality of Life of Pregnant Women - Sajad Basharpoor; Hadis Heidarirad; Esmael Soleimani; Behroz Degdar (Golestan University of Medical Sciences, 2017)
Introduction: High quality of life during the pregnancy is of great importance for both mother and the fetus. In order to identify factors affecting the quality of life of pregnant women, this study was conducted to show the role of health promoting behaviors in predicting the quality of life of pregnant women. Methods: This was a cross sectional study. Statistical population consisted of all pregnant women who had referred to the Health Centers of Gilan-e Gharb City for receiving the prenatal care from March 2013 to September 2013, of whom, 90 people were selected by purposive non-random sampling method and data were collected by questionnaires of Health Promoting and Short Form 36 Quality of Life Questionnaire (SF-36). The data were analyzed by Pearson correlation coefficient and multiple regression analysis.  Results: The mean and standard deviation age (SD) of the pregnant women was 26.72 ± 4.45. There was a positive relationship between quality of life of pregnant women and an overall score of health promoting behaviors and variables of heath responsibility, good nutrition, spiritual growth, interpersonal relationships and stress management (P<0.005). Regression analysis also showed that 37% of the total variance in the quality of life of pregnant women is explained by interpersonal behaviors. Conclusion: Results of this study show that health responsibility, good nutrition, spiritual growth, interpersonal relationships and stress management improve quality of life of pregnant women. Of these styles, interpersonal relationships play an important role in predicting quality of life. These results highlight the importance of training the health promoting behaviors notably effective interpersonal relationships during pregnancy.